1992
DOI: 10.1159/000182315
|View full text |Cite
|
Sign up to set email alerts
|

Bone Turnover in Overt and Subclinical Hyperthyroidism Due to Autonomous Thyroid Adenoma

Abstract: Parameters of bone turnover were measured in 20 premenopausal women affected by autonomous thyroid adenoma: 7 patients were suffering from overt hyperthyroidism with raised values of free thyroid hormones; 13 were clinically euthyroid and had normal values of free thyroid hormones. In all cases serum TSH concentrations were below the lower normal limit of our laboratory ( < 0.4 mU/l). Eleven healthy premenopausal women were studied as a control group. Patients with overt hyperthyroidism disclosed a significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 5 publications
1
18
0
Order By: Relevance
“…In contrast to these studies, De Menis et al reported that patients with overt hyperthyroidism displayed a significant enhancement of both bone resorption (increased serum calcium and urinary excretion of hydroxyproline) and bone formation (increased serum levels of osteocalcin and alkaline phosphatase) when compared both to controls and to patients with subclinical hypothyroidism, and that no significant alterations of bone metabolism parameters were found in patients with subclinical hyperthyroidism in comparison with healthy controls [16]. Similarly, Gurlek and Gedik reported that endogenous subclinical hyperthyroidism is not associated with increased bone turnover, and bone mineral density is not reduced in premenopausal women, at least in the short term [17].…”
Section: Discussionmentioning
confidence: 91%
“…In contrast to these studies, De Menis et al reported that patients with overt hyperthyroidism displayed a significant enhancement of both bone resorption (increased serum calcium and urinary excretion of hydroxyproline) and bone formation (increased serum levels of osteocalcin and alkaline phosphatase) when compared both to controls and to patients with subclinical hypothyroidism, and that no significant alterations of bone metabolism parameters were found in patients with subclinical hyperthyroidism in comparison with healthy controls [16]. Similarly, Gurlek and Gedik reported that endogenous subclinical hyperthyroidism is not associated with increased bone turnover, and bone mineral density is not reduced in premenopausal women, at least in the short term [17].…”
Section: Discussionmentioning
confidence: 91%
“…Some studies reported that subclinical hyperthyroid patients with nodular goiter showed accelerated bone loss at a rate of about 2% per year [12, 25], while others showed that no significant alteration of bone metabolism parameters was found in subclinical hyperthyroid patients when compared with healthy controls [14, 23]. …”
Section: Discussionmentioning
confidence: 99%
“…The major problem in assessing adverse skeletal effects of SHyper is the difficulty in establishing disease duration. There are conflicting results related to bone mineral density (BMD) [96,97,98,99,100,101,102,103,104]. However, the majority of studies show that Endo SHyper does not affect BMD in premenopausal women [96,97,98], whereas a decreased BMD has been reported in postmenopausal women [99,100,101,102,103,104].…”
Section: Risks Associated With Persistent and Untreated Endo Subclinimentioning
confidence: 99%